Quality Costs and Their Costing in Times of COVID-19 Pandemic in Independent Hospitality Services: Case Study of The Harmony Polish Hotels Group - Wojciech SADKOWSKI; Krzysztof SALA (Communications of International Proceedings, 2022)
The aim of the publication is to discuss the complexity of the issue of quality costs and their costing in the difficult period of the Covid - 19 pandemic on the example of the hospitality industry. To achieve the objectives of the publication, the analysis was conducted on one of the hotel organisations in Poland, the Harmony Polish Hotels consortium. This organisation unites only non chain hotels. The article uses the method of direct interview. The vast majority of member facilities of the organisation in question participated in the survey. The analysis of the survey results provided many interesting conclusions and observations on the functioning of individual member facilities.